Garbage, narration, reading. Alfred Döblin’s Die Ermordung einer Butterblume and its contexts - David-Christopher Assmann (RiCognizioni, 2019)
Döblin’s short prose Die Ermordung einer Butterblume follows a poetic of garbage. The text not only has a strong interest in practices of eliminating broken materiality but also participates in textual presentations of garbage as found in contemporary discourses of hygiene. Both aspects taken together make it possible to correlate the multitude of different readings of the short story with its technique. Focused on garbage, the text poetically captures the asyndetic arrangement of both the elements of its syntagma and its cultural paradigms in which it is located.